Comparing the Academic Performance of High School Athletes and Non-Athletes in Kansas 2008-2009 - Angela Lumpkin; Judy Favor (Journal of Applied Sports Management, 2013)
The academic performance of students in grades 9-12 who did or did not participate in high school sports in Kansas during the 2008-2009 school year was analyzed. In addition to overall comparisons between athletes and non-athletes on GPAs, graduation rates, number of dropouts, ACT test scores, and state assessments, some gender, ethnicity, and grade comparisons were made. High school athletes earned higher grades, graduated at a higher rate, dropped out of school less frequently, and scored higher on state assessments than did non-athletes; results on the ACT were mixed. Differences between athletes and non-athletes were found for males and females across all academic performance measures, with females contributing more to the differences between athletes and non-athletes on GPAs and not dropping out of school. Whites contributed more to the differences between non-athletes and athletes than did the other racial categories for GPAs, graduation rates, and not dropping out of school.
Keywords: High school; Athletes versus non-athletes; Academic performance.